2016
DOI: 10.5603/ait.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in intensive care unit patients — a single-centre, 3-year observational study according to the INICC project

Abstract: In the observed period of time, the incidence of CA-UTI was higher than in the INICC (2014) report and the NHSN/CDC (2012) report. Analysis of compliance with a "Urinary Catheter Bundle" to prevent UTI shows low implementation of preventative methods with the INICC protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
2
13
2
5
Order By: Relevance
“…CAUTI rate was 36.2 per 1000 catheter days which was higher than that reported by Sabir et al, Duszyńska et al, Derya keten et al 5,25,26 who reported a CAUTI rate of 3.65, 7.16 and 9.6 per 1000 catheter days respectively and it is not meeting the NHSN standard too. This may be due to better infrastructure, availability of trained staff, strict infection control practices and an appropriate antibiotic policy, proper guided bundle care for both procedure and maintenance of catheter which we are planning to implement.…”
Section: Discussioncontrasting
confidence: 52%
“…CAUTI rate was 36.2 per 1000 catheter days which was higher than that reported by Sabir et al, Duszyńska et al, Derya keten et al 5,25,26 who reported a CAUTI rate of 3.65, 7.16 and 9.6 per 1000 catheter days respectively and it is not meeting the NHSN standard too. This may be due to better infrastructure, availability of trained staff, strict infection control practices and an appropriate antibiotic policy, proper guided bundle care for both procedure and maintenance of catheter which we are planning to implement.…”
Section: Discussioncontrasting
confidence: 52%
“…12 ). The third most common form of healthcare-associated infection was urinary tract infection (UTI); according to Duszyńska et al 24 , the incidence of UTI in single-centre studies was 7% and was 92% in patients with urinary catheters. Our study obtained slightly lower values, with an incidence of UTI of 4% (incidence density 5) and with association with the urinary catheter in 99% of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…(%22), Acinetobacter baumannii (%20), Klebsiella pneumoniae (%18) ve Kandida spp. (%13) olduğu tespit edilmiştir [7]. İran' da yapılan çalışmada ise YBÜ' deki hastaların idrar kültürlerinde en fazla üreyen patojenlerin sırasıyla E. coli (%34.9), klebsiella spp.…”
Section: Sondayla İlişkili İdrar Yolu Enfeksiyonları: Farklı Hasta Pounclassified